Enabling an environment for solar and wind energy deployment in the Macedonian agricultural sector - Markovska, Natasa; Krkoleva, Aleksandra; Taseska, Verica; Borozan, Vesna; Pop-Jordanov, Jordan (AIP Publishing, 2013)
The paper deals with the possibility for cross-cutting the agricultural and energy sector, aiming toward better utilisation of the available renewable energy sources. An integrated methodological framework is proposed in order to formulate the possible solutions to the core question, which is "who does what" to improve the utilization of renewable energy potential in the agricultural sector. The methodology includes mainly stakeholder analyses (focusing on importance, knowledge, position, and interests of each stakeholder), as well as problem and objective tree analyses. It is applied for the case of solar and wind energy deployment in the Macedonian agricultural sector. The creation of "enabling environment" is a complex process which involves different stakeholders, with specific roles and assignments, but acting in partnership with one another. Implicitly, some recommendations in a form of priority actions with roles and responsibilities assigned to various stakeholders are proposed in the paper.
Keywords: Agricultural sector, Complex Processes, Cross-cutting, Methodological frameworks, Renewable energy potentials, Renewable energy source, Solar and wind energies, Stakeholder analysis